"My young life, finished already?": a qualitative study of embedded social stressors and their effects on mental health of low-wage male migrant workers in Singapore - Aysha Farwin; Amanda Low; Natasha Howard; Huso Yi (BMC, 2023)
Abstract Background Increasing evidence shows low-wage migrant workers experience a high prevalence of mental health disorders and adverse health outcomes. Significant disparities in health services usage among migrant workers create added vulnerability to health complications. However, much remains unclear about how vulnerabilities are constructed in migrant worker populations. Additionally, no studies in Singapore have attempted to critically examine the degree to which social environment and structures affect the health and wellbeing of migrant workers. Therefore, this study aimed to critically situate the socio-structural factors creating conditions of vulnerability among migrant workers using a social stress perspective. Methods We conducted semi-structured individual and group interviews with migrant workers focused on individual life experiences, community experiences (individual and collective social capital), health (mental and physical health concerns) and stress response behaviours. We used a grounded theory approach to identify sources of stress and stress responses and uncover pathways to social vulnerabilities. Results Findings from 21 individual and 2 group interviews revealed that migrant workers were embedded in a cycle of chronic stress driven by structural factors that were mutually reinforced by stressors arising from their social environment. Socio-structural stressors enacted as poor living, working and social conditions resulted in their negative quality-of-life appraisal. Stressors arising from being "foreign" resulted in anticipated stigma, concealment, and healthcare avoidance. These factors synergistically created a persistent mental health burden for migrant workers. Conclusions Findings highlight the need to address the mental health burden placed on migrant workers and create avenues for migrant workers to seek psychosocial support to manage their stressors.